Stability, antioxidant and antimicrobial activities of ginger essential oil nanoemulsion: Impact of droplet size and concentration with molecular dynamics insights into zingiberene bioactivity - Olunusi, Samuel Olugbenga; Nor Hanuni, Ramli; Fatmawati, Adam; Rahmadhia, Safinta Nurindra (Elsevier, 2025)
This study synthesized ginger essential oil (GEO) nanoemulsions, F1@5, F2@10, and F3@5, using high-pressure homogenization to investigate the effects of droplet size and oil concentration on stability and bioactivity. Results revealed that smaller droplet size had a significantly greater impact (p < 0.05) than concentration in enhancing stability and functional performance. Formulation F2@10, with the smallest droplet size (62.08 nm), exhibited superior stability and uniform microstructure compared to F1@5 (141.83 nm) and F3@5 (133.35 nm). Fourier-transform infrared (FTIR) spectroscopy indicated minimal changes in functional groups, confirming stable molecular interactions essential for maintaining bioactivity. F2@10 showed the highest antioxidant activity (26.58 % DPPH radical scavenging) and antifungal efficacy (55.16 % mycelial growth inhibition), attributed to enhanced surface area from reduced droplet size. Density functional theory (DFT) analysis of zingiberene, a major GEO component, revealed a moderate energy gap (5.19 eV), ionization potential (5.88 eV), and stable frontier orbital energies (HOMO: −5.88 eV; LUMO: −0.69 eV), supporting its potential for redox interactions. Field emission scanning electron microscopy (FESEM) and 30-day stability studies further confirmed F2@10's structural integrity and sustained antioxidant activity. These findings underscore the importance of formulation parameters in optimizing GEO nanoemulsions for therapeutic applications against oxidative stress and microbial threats.